2006
DOI: 10.1213/01.ane.0000184045.01780.73
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Observational and Objective Measures to Differentiate Depth of Sedation in Children from Birth to 18 Years of Age

Abstract: Several observational and objective methods are available to assess sedation depth; however, data regarding their accuracy in differentiating deep sedation are limited. In this study we compared 3 sedation tools in children from birth to 18 yr of age and determined their relative value in detecting deep levels of sedation. Bispectral index monitoring (BIS), Modified Maintenance of Wakefulness Tests (MMWT), and the University of Michigan Sedation Scale (UMSS) were used to assess sedation. Three-hundred-twenty-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 23 publications
1
43
0
1
Order By: Relevance
“…A variety of sedation scoring systems have been developed to measure the depth of sedation for both research and clinical settings. The more commonly used scales include the University of Michigan Sedation Scale ( UMSS ), 9,10 the Observer's Assessment of Alertness/Sedation (OAA/S ), 11 the Ramsay Sedation Score, 12 and the Houpt Scale. 13 These sedation scales have limitations in clinical practice because of observer variance in the subjective assessment and the disruptive effect of stimuli that need to be given to assess the depth of sedation.…”
mentioning
confidence: 99%
“…A variety of sedation scoring systems have been developed to measure the depth of sedation for both research and clinical settings. The more commonly used scales include the University of Michigan Sedation Scale ( UMSS ), 9,10 the Observer's Assessment of Alertness/Sedation (OAA/S ), 11 the Ramsay Sedation Score, 12 and the Houpt Scale. 13 These sedation scales have limitations in clinical practice because of observer variance in the subjective assessment and the disruptive effect of stimuli that need to be given to assess the depth of sedation.…”
mentioning
confidence: 99%
“…All demographics and hospitalization details, including pain and sedation scores every 4 hours and daily opioid administration (measured in morphine equivalents), were recorded through review of the electronic medical record (EMR). Pain scores that had been recorded using either the Numeric Rating Scale (NRS) or the Wong-Backer Faces Scale, and sedation scores that had been assessed utilizing The University of Michigan Sedation Scale (UMMS) were documented during the chart review [21,22]. Comorbidities such as history of asthma, priapism, kidney disease, or avascular necrosis, were also recorded from the EMR.…”
Section: Research Design and Data Sourcesmentioning
confidence: 99%
“…Use of BIS during procedures that require sedation in children Several studies have demonstrated the utility of BIS to control the level of sedation when performing invasive procedures in children, finding a good correlation with clinical scales such as the sedation agitation scale, Ramsay Scale, and University of Michigan scale [10,21,36,37]. Values of BIS around 70 are considered appropriate [32].…”
Section: Bispectral Indexmentioning
confidence: 99%